Polymer-based nanosystems and their applications in bone anticancer therapy - Nafo, Wanis (Frontiers in Chemistry, 2023)
The mortality rate of bone cancer has witnessed a substantial reduction in recent years, all thanks to the advent of advanced cancer treatment modalities such as surgical intervention, radiation, and chemotherapy. Nevertheless, these popular modalities come with a set of clinical challenges, including non-specificity, side effects, and drug intolerance. In recent years, polymer-based nanosystems have emerged as a promising solution in bone anti-cancer therapy by virtue of their unique physical and chemical properties. These nanosystems can be tailored for use in different drug release mechanisms for therapeutic implementations. This review delves into the efficacy of these therapy applications in bone cancer (with a focus on one of the most common types of cancers, Osteosarcoma) treatment and their correlation with the properties of polymer-based nanosystems, in addition to their interaction with the tumor microenvironment and the biological milieu.